Analisis Tingkat Pengetahuan dalam Pemanfaatan Layanan Mobile JKN - Nurhidayah, Nurhidayah; Purba, Quen Kholisa; Nugraha, Raihan; Gurning, Fitriani Pramita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
the JKN mobile application is an application that can be accessed via a smartphone. The JKN mobile application is the latest innovation from Health BPJS in improving a service to the community, especially in the health sector, but many people have not used this application to find out the services and knowledge of the community using the JKN mobile application service and to examine the effectiveness of using the JKN mobile application for the community writing this journal article using the article search method using two databases, namely Google Scholar and PubMed Health with the keyword service utilization, mobile JKN. mandatory application of health services in Indonesia through digitization which also facilitates membership registration to obtain health services in the form of individual health counseling, immunization, family planning and effective health screening, so that people in Indonesia will be evenly distributed or at least reach 98% can become participants by using JKN mobile as the quality of health services. The quality of mobile JKN health services raises the satisfaction of health service users. the results of the research by experts show that mobile health insurance has satisfactory quality for its use. However, many people still don't know about this JKN application. Keywords: Utilization of services, Mobile JKN, Health